Occupational Stress and Work-Life Balance of The High School Teachers - Charlene C. Pita (Alliance oh Health Activists (AloHA), 2019)
Background: Work stress is what one gets from doing a job or profession like being a teacher. Work stress may be harmful both physical and, or emotional. In today’s generation of working professionals, occupational stress is a significant issue. The increasing incidence of stress among teachers, in particular, has adversely affected their work performance and how they maintain a balance between personal lives and work. Objectives: This purpose of this study was to determine the level of stress at work and the balance between work and private life and its relation to the Job performance of selected high school teachers. Methods: This quantitative research used a descriptive research approach is used in administering the questionnaire to determine the level of professional stress, the perceived balance between professional and private life, and the teaching performance of secondary teachers. The population of the study participated in 106 Secondary Teachers. The researcher made sure that the instrument is conducted to the respondents and carefully follow the procedure. Their responses were tallied and treated to the following statistical treatment used are as follows: Ranking is to determine the relationship between a set of items and also to determine the profile of the respondents through the computation of frequency and percentage, Weighed is to gauge the average value of responses to items in the questionnaire; Pearson Product Moment Correlation and Chi-square Test is to determine the significant degree of relationship between teachers’ profile and occupational stress, work-life balance, and job performance, to further test the considerable result of the Pearson Product Moment Correlation, the computed data are subjected to t-test wherein the computed t-test is compared to the tabular value of significance with the specified degree of freedom. The questionnaire is a standardized test and tested in Cronbach alpha with a value higher than .60. Results: This study revealed that the occupational stress of secondary school teachers does not exceed very high levels of occupational stress. All six dimensions of occupational stress – supports, demands, change, relationships, control, and role, contribute only marginally to the overall stress experienced by the respondents. It showed in the result and interpreted as Slightly Stressed of the overall composite mean. The respondent teachers perceive their work-life balance, in terms of work spillover in personal life (WSPL) and personal life spillover in work (PLSW) to be Good. From these findings, the researcher can infer that secondary school teachers can strike the right balance between their work life and personal life. However, there is still a lot of room for improvement before the respondents can be able to achieve a perfect and excellent work-life balance. This study is deemed beneficial to specific individuals and a group of people: high school teachers, principals, students, parents, and other academic leaders and institutions. Keywords: Occupational, Stress, High school teacher, Performance, Personal and work